A 3D bioinspired highly porous polymeric scaffolding system for in vitro simulation of pancreatic ductal adenocarcinoma. Issue 37 (7th June 2018) - Totti, Stella; Allenby, Mark C.; Dos Santos, Susana Brito; Mantalaris, Athanasios; Velliou, Eirini G.
Abstract : A 3D biomimetic model for in vitro studies of pancreatic cancer. Abstract : Pancreatic ductal adenocarcinoma is an aggressive disease with an extremely low survival rate. This is due to the (i) poor prognosis and (ii) high resistance of the disease to current treatment options. The latter is partly due to the very complex and dense tissue/tumour microenvironment of pancreatic cancer, which contributes to the disease's progression and the inhibition of apoptotic pathways. Over the last years, advances in tissue engineering and the development of three-dimensional (3D) culture systems have shed more light into cancer research by enabling a more realistic recapitulation of the niches and structure of the tumour microenvironment. Herein, for the first time, 3D porous polyurethane scaffolds were fabricated and coated with fibronectin to mimic features of the structure and extracellular matrix present in the pancreatic cancer tumour microenvironment. The developed 3D scaffold could support the proliferation of the pancreatic tumour cells, which was enhanced with the presence of fibronectin, for a month, which is a significantly prolonged in vitro culturing duration. Furthermore, in situ imaging of cellular and biomarker distribution showed the formation of dense cellular masses, the production of collagen-I by the cells and the formation of environmental stress gradients ( e.g. HIF-1α) with similar heterogeneity trends to the ones reported in in vivo studies. The results obtained in this study suggest that this bioinspired porous polyurethane based scaffold has great potential for in vitro high throughput studies of pancreatic cancer including drug and treatment screening.